Chlorproguanil-dapsone: effective treatment for uncomplicated falciparum malaria. - Amukoye, E (1997)
Pyrimethamine-sulfadoxine, the first choice for uncomplicated falciparum malaria in Africa, exerts strong selection pressure for resistance because of its slow elimination. It is likely that resistance will emerge rapidly, and there is no widely affordable replacement. Chlorproguanil-dapsone is cheap, rapidly eliminated, more potent than pyrimethamine-sulfadoxine, and could be introduced in the near future to delay the onset of antifolate resistance and as "salvage therapy" for pyrimethamine-sulfadoxine failure. A total of 448 children were randomly allocated (double blind) to either a single dose of pyrimethamine-sulfadoxine or to one of two chlorproguanil-dapsone regimens: a single dose or three doses at 24-h intervals. Reinfections are clinically indistinguishable from recrudescence and are more likely after treatment with rapidly eliminated drugs; we measured the incidence of parasitemia in 205 initially aparasitemic children to allow comparison with the three treatment groups. The patients and a community surveillance group were followed up for 28 days. At the study end point, 31.2% (95% confidence interval, 24.9-38.0) of the community surveillance group subjects were parasitemic, compared with subjects in the treatment groups, whose rates of parasitemia were 40.8% (32.9-49.0; relative risk [RR], 1.31 [0.99-1.73]) after triple-dose chlorproguanil-dapsone, 19.7% (13.5-27.2; RR, 0.63 [0.43-0.93]) after pyrimethamine-sulfadoxine, and 65.6% (57.5-73.0; RR, 2.10 [1.66-2.65]) after single-dose chlorproguanil-dapsone. Pyrimethamine-sulfadoxine and triple-dose chlorproguanil-dapsone were effective treatments. Pyrimethamine-sulfadoxine provided chemoprophylaxis during follow-up because of its slow elimination. Triple-dose chlorproguanil-dapsone should now be developed in an attempt to reduce the rate of emergence of antifolate resistance in Africa and for affordable salvage therapy in cases of pyrimethamine-sulfadoxine failure.